Secreted heat shock protein gp96-Ig and OX40L-Fc combination vaccine enhances SARS-CoV-2 Spike (S) protein-specific B and T cell immune responses. (December 2022) - Padula, Laura; Fisher, Eva; Rivas, Katelyn; Podack, Kristin; Frasca, Daniela; Kupritz, Jonah; Seavey, Matthew M.; Jayaraman, Padmini; Dixon, Eric; Jasuja, Rahul; Strbo, Natasa
Graphical abstract: A cell-based vaccine co-secreting gp96-Ig, protein S1 and OX40L-Fc leads to activation of dendritic cells (DC) and cross-presentation of gp96-chaperoned protein S peptides to CD8+ T cells. Co-secretion of OX40L-Fc further augments CD8+T cell activity through OX40/OX40L axis. Secreted protein S1 is endocytosed by activated DC and S1 peptides are presented within the MHC class II molecules to TFH cells that also receive co-stimulatory signals through OX40L-Fc. In addition, B cells recognize secreted protein S1 through BCR and present S1 peptides within the MHC class II molecules to TFH cells. TFH cells through OX40/OX40L axis provide essential signals to promote B cell differentiation into memory B cells and long-lived plasma cells, and secretion of high-affinity specific antibodies. Local modulation of the gp96-Ig vaccine microenvironment by OX40L-Fc has the advantage to enhance immunological protection through providing additional support to CD8+ T cell and immunoglobulin antiviral response in the lungs and simplifying the clinical translation of such combination immunotherapies into humans. Highlights: gp96-Ig-S-OX40L-Fc vaccine enhances S-specific IgG responses. gp96-Ig-S-OX40L-Fc vaccine enhances TFH cell responses. gp96-Ig-S-OX40L-Fc vaccine enhances lungs S-specific CD8 + T cell responses. Abstract: Encouraging protection results from current mRNA-based SARS-CoV-2 vaccine platforms are primarily due to the induction of SARS- CoV-2- specific B cell antibody and CD4 + T cell. Even though, current mRNA vaccine platforms are adept in inducing SARS-CoV2-specific CD8 + T cell, much less is known about CD8 T cells contribution to the overall vaccine protection. Our allogeneic cellular vaccine, based on a secreted form of the heat-shock protein gp96-Ig, achieves high frequencies of polyclonal CD8 + T cell responses to tumor and infectious antigens through antigen cross-priming in vivo . We and others have shown that gp96-Ig, in addition to antigen-specific CD8 + T cell anti-tumor and anti-pathogen immunity, primes antibody responses as well. Here, we generated a cell-based vaccine that expresses SARS-Cov-2 Spike (S) protein and simultaneously secretes gp96-Ig and OX40L-Fc fusion proteins. We show that co-secretion of gp96-Ig-S peptide complexes and the OX40L-Fc costimulatory fusion protein in allogeneic cell lines results in enhanced activation of S protein-specific IgG antibody responses. These findings were further strengthened by the observation that this vaccine platform induces T follicular helper cells (TFH) and protein-S -specific CD8 + T cells. Thus, a cell-based gp96-Ig vaccine/OX40-L fusion protein regimen provides encouraging translational data that this vaccine platform induces pathogen-specific CD8+, CD4 + T and B cell responses, and may cohesively work as a booster for FDA-approved vaccines. Our vaccine platform can be rapidly engineered and customized based on other current and future pathogen sequences.